Experiment and Applications of Dynamic Constitutive Model of Tensile and Compression Damage of Sandstones - Chunliang Dong; Xiaoyu Lu; Guangming Zhao; Xiangrui Meng; Yingming Li; Xiang Cheng (Advances in Materials Science and Engineering)
A dynamic constitutive model of tensile and compressive damage was constructed on the basis of the ZWT and statistical damage models, particularly by introducing the maximum tension and maximum shear stress criteria to solve the failure problem of the surrounding rock mass caused by deep excavation unloading. A shock compression and splitting test of sandstone specimens under different strain rates were performed by using a split Hopkinson pressure bar (SHPB). The constitutive model was developed again by LS-DYNA for the secondary numerical impact compression and split test of sandstones. Results demonstrated that the constructed dynamic constitutive model of tensile and compressive damage could considerably simulate tensile and compressive stress-strain relations and failure features of sandstones well. Lastly, the constitutive model was applied to conduct a numerical study on damage distribution and failure laws of the surrounding rocks at Gaochou Roadway, Luling Mine under cyclic excavation unloading. Results showed that the unloading failure of surrounding rocks has significant accumulation effects, and the accumulated damage on the floor is larger than those on the roof and roadway walls. The maximum breaking and damage depths are 0.4 m and 5.31 m, respectively. Circumferential damage showed an “umbrella-shaped” distribution pattern. With respect to trend, the damage accumulation effect at the rear part of the excavation face is stronger than that at the front part and the maximum influence distance is 6.4 m. However, the influencing degree of the accumulation effect attenuates gradually as advancing into the excavation face. The reliability of the numerical simulation is verified by combining the test results of the field geological radar on the roadway roof.